Response of Cucumber CU 699 to Solid Organic Fertilizer Waste Meal Worm Frass and Corn Cob Biochar - Laili, Saimul; Fikriyah, Khafivatul; Tito, Sama ’ Iradat (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
The cucumber plant (Cucumis sativus L.) is one of the plants that has high economic prospects in Indonesia. The use of cucumber plants is known in various health, beauty, and consumption industries, but over the years cucumber production has decreased due to various things, one of which is the cultivation system. Frass and corn cobs are waste that can be processed into fertilizer and biochar, where this material can restore the revitalization of agricultural land and support growth. The purpose of this study is to analyze the response of cucumber plants CU 699 to the use of solid organic fertilizer for the waste of frass mealworm and corn cob biochar, as well as to determine the best treatment for plant growth. This study uses the Petal Random Design (RAK) method. Data analysis using One Way ANOVA and Tukey HSD follow-up test. The parameters measured include the number of leaves, leaf size, stem height, root length, and dry weight of the plant. The results showed that the application of mealworm frass and corn cob biochar had an effect on plant growth. The best treatment for cucumber growth is at P3B3.